Front Cover Picture: Biocatalytic Application of a Membrane‐Bound Coumarin C‐Glucosyltransferase in the Synthesis of Coumarin and Benzofuran C‐Glucosides (Adv. Synth. Catal. 22/2021). Issue 22 (29th September 2021) - Chen, Dawei; Fan, Shuai; Yang, Zhaoyong; Dai, Jungui
Abstract : The front cover picture, designed by D. Chen and J. Dai, illustrates the enzymatic synthesis of coumarin C‐glucosides by a membrane‐bound C‐glucosyltransferase MaCGT from Morus alba, a traditional Chinese medicinal herb. The whole‐cell biocatalyst harboring MaCGT were developed and displayed efficiently regio‐ and stereo‐specific C‐glucosylation capacity towards structurally different coumarins. Details can be found in the communication by Dawei Chen and co‐workers (D. Chen, S. Fan, Z. Yang, J. Dai, Adv. Synth. Catal . 2021, 363, 5072–5078; DOI: 10.1002/adsc.202100041 ).